A Fourier transform infrared trace gas and isotope analyser for atmospheric applications - Griffith, David W. T.; Hammer, Samuel (Atmospheric measurement techniques, 2012)
Concern in recent decades about human impacts on Earth's climate has led to the need for improved and expanded measurement capabilities of greenhouse gases in the atmosphere. In this paper we describe in detail an in situ trace gas analyser based on Fourier Transform Infrared (FTIR) spectroscopy that is capable of simultaneous and continuous measurements of carbon dioxide (CO2), methane (CH4), carbon monoxide (CO), nitrous oxide (N2O) and 13C in CO2 in air with high precision. High accuracy is established by reference to measurements of standard reference gases. Stable water isotopes can also be measured in undried airstreams. The analyser is automated and allows unattended operation with minimal operator intervention. Precision and accuracy meet and exceed the compatibility targets set by the World Meteorological Organisation - Global Atmosphere Watch for baseline measurements in the unpolluted troposphere for all species except 13C in CO2. The analyser is mobile and well suited to fixed sites, tower measurements, mobile platforms and campaign-based measurements. The isotopic specificity of the optically-based technique and analysis allows its application in isotopic tracer experiments, for example in tracing variations of 13C in CO2 and 15N in N2O. We review a number of applications illustrating use of the analyser in clean air monitoring, micrometeorological flux and tower measurements, mobile measurements on a train, and soil flux chamber measurements.